Factors contributing to the reduction in childhood stunting in Bangladesh: a pooled data analysis from the Bangladesh demographic and health surveys of 2004 and 2017–18 - Pradeep Kumar (BMC, 2021)
Abstract Background Over the last two decades, Bangladesh has made progress in reducing the percentage of stunted children under age 5 years from 51% in 2004 to 31% in 2017. Such reduction has created a source for new research to understand its contributing factors. The present study aims to identify such crucial factors which contributed in reducing the percentage of under-five stunting status of children from 2004 to 2017–18. Methods The study used data from the Bangladesh Demographic and Health Surveys (BDHS), conducted in 2004 and in 2017–18, focused on children under-5-years of age (U5). The sample sizes were n = 6375 children included in the 2004 survey and n = 8312 children included in the 2017–18 survey. Descriptive analysis and bivariate analysis were conducted for a general characterization of the samples. Logistic regression was used to find out the significant factors contributing to the prevalence of stunting among U5 children. Furthermore, the Fairlie decomposition technique was used to identify the crucial factors that contributed to the reduction of stunting. Results The prevalence of stunting among U5 children has declined significantly, from 49.8 to 30.7% between the two survey periods (2004 and 2017–18). Estimates of decomposition analysis show that overall, the selected variables explained 50.6% of the decrease in the prevalence of stunting. Mother’s characteristics such as age at first birth, education level, working status and BMI (body mass index) status were the primary contributors of this change. Father’s characteristics, such as education explained 9% of this change. Conclusion The results of the study highlight the importance of increasing maternal education and reducing inter-household wealth inequality to improve nutritional status of U5 children. In order to achieve further reduction in stunting, among U5 children in Bangladesh, this paper calls for policymakers to develop effective programs to improve maternal education, raise parental awareness of parents regarding children’s height and weight, and aim to significantly reduce inter-household inequalities.